CHANGE MANAGEMENT - THE APLICATIVE CONTEXT OF THE FACTORS WHICH DECISIVELY INFLUENCE THE QUALITY OF EDUCATIONAL ACT - Emil LAZĂR; Ionel Florian LIXANDRU (Universitaria Publishing House, Craiova, 2020)
Romanian pre-university education, is at the point when it needs a rethinking, a reconsideration, a change. We speak about a necessity imposed by the endogenous factors of system, but required by external aspects of educational system, by the interaction of education with social subsystems and challenges humanity. The article proposes a definition of change, of the structural elements susceptible to the change process and of the systematic approach, according to witch this change may take place within Romanian pre-university education